PENGARUH PENDAPATAN MASYARAKAT, PENETRASI GEOGRAFIS PERBANKAN, PENETRASI DEMOGRAFIS PERBANKAN, PENGGUNAAN REKENING KREDIT DAN PENGGUNAAN REKENING DPK BANK UMUM TERHADAP KREDIT UMKM DI INDONESIA PERIODE TAHUN 2013-2017 - Dina, Anisa Puspa; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2019)
This study was conducted to examine the impact of Public Income, Geographic BranchPenetration (GBP), Demographic Branch Penetration (DBP), Credit Account per Capita(CAC), and Deposit Account per Capita (DAC) of commercial banks on Credit of MicroSmall Medium Enterprise.The sample used in this study are 33 Provinces in Indonesia in the period 2013-2017 usingpurposive sampling technique. The data examined uses the method of non-participantobservation by directly quoting financial, GRDP, banking, geographical, and demographicdata. The analysis used in this research is multiple linear regression consisting of theclassic assumption test, F test, t test, and hypothesis testing.The results of this study indicate that Income, Credit Account per Capita, and DepositAccount per Capita have a positive and significant effect on MSME credit, whileGeographical Banking penetration has a positive but not significant effect on MSMEcredit, and Banking Demographic Penetration has a significant negative effect on MSMEcredit